Harmonization and Side Payments in Political Cooperation - Harstad, Bård (American Economic Review, 2007)
For two districts or countries that try to internalize externalities, I analyze a bargaining game under private information. I derive conditions for when it is efficient with uniform policies across regions—with and without side payments—and when it is efficient to prohibit side payments in the negotiations. While policy differentiation and side payments allow the policy to better reflect local conditions, they create conflicts between the regions and, thus, delay. The results also describe when political centralization outperforms decentralized cooperation, and they provide a theoretical foundation for the controversial “uniformity assumption” traditionally used by the fiscal federalism literature. (JEL C78, D72, D82, H77)